Comparison of high resolution T2W and Gd-T1W of MRI internal acoustic canal in sensorineural hearing loss - Panida Charnchaowanish (2018)
© 2016, Medical Association of Thailand. All rights reserved. Objective: To evaluate the concordance of high resolution T2-weighted (HR-T2W) and Gd-T1W for mass detection in internal acoustic canal (IAC) or cochlear in sensorineural hearing loss (SNHL). Material and Method: The retrospective study of patients with SNHL undergoing magnetic resonance imaging (MRI) IAC protocol was performed. HR-T2W and Gd-T1W were separately reviewed for any mass in IAC or cochlear. Results: One hundred eight cases were available for evaluation with 43 males and 65 females (mean age of 56.04 years old; range 15 to 86 years old). Symptoms of SNHL on right side were 39 cases (36.1%), left side 39 cases (36.1%), both sides 15 cases (13.9%), and asymmetric SNHL 15 cases (13.9%). Twenty two (20.4%) cases had mass in IAC and/or cochlear demonstrated on both HR-T2W and Gd-T1W. No discrepancy of abnormality detection between both pulse sequences was found. Conclusion: HR-T2W was as accurate as Gd-T1W in detecting mass in IAC and cochlear in patients with SNHL. Screening with HR-T2W could be used with confidence and might be reasonable to reducing cost of the MRI study in appropriate setting of patients presenting with SNHL.